2018
DOI: 10.1155/2018/5057624
|View full text |Cite
|
Sign up to set email alerts
|

Fat Embolism and Nonconvulsive Status Epilepticus

Abstract: Fat embolism syndrome (FES) typically occurs following orthopedic trauma and may present with altered mental status and even coma. Nonconvulsive status epilepticus is an electroclinical state associated with an altered level of consciousness but lacking convulsive motor activity and has been reported in fat embolism. The diagnosis is clinical and is treated with supportive care, antiepileptic therapy, and sedation. A 56-year-old male presented with altered mental status following internal fixation for an acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Damage to the retina, kidney, liver, and heart has been reported, although the triad of petechial hemorrhages, respiratory distress, and altered mental status is the most common clinical presentation [ 1 - 2 ]. Cutaneous manifestations take on the form of a petechial vest-like structure in the axillary or trunk region and occur in up to 50-60% of cases but can be transient [ 1 , 7 - 8 ]. Pulmonary complications occur in up to 75% of cases, and 39% of patients develop severe hypoxemic respiratory failure that can be indistinguishable from acute respiratory distress syndrome [ 1 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Damage to the retina, kidney, liver, and heart has been reported, although the triad of petechial hemorrhages, respiratory distress, and altered mental status is the most common clinical presentation [ 1 - 2 ]. Cutaneous manifestations take on the form of a petechial vest-like structure in the axillary or trunk region and occur in up to 50-60% of cases but can be transient [ 1 , 7 - 8 ]. Pulmonary complications occur in up to 75% of cases, and 39% of patients develop severe hypoxemic respiratory failure that can be indistinguishable from acute respiratory distress syndrome [ 1 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical presentation and ultimate prognosis of CFE are variable and depend on the disease burden. Patients with acute respiratory distress syndrome generally have the worst prognosis, as most deaths are attributed to respiratory failure [ 1 , 7 ]. This was evident in the presented case, as the patient’s worsening respiratory failure contributed to mortality despite an early diagnosis of CFE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported nonconvulsive status epilepticus (NCSE) secondary to FES. 14,20,21 NCSE shows only the presence of an altered consciousness but lacks convulsive motor activity; thus, EEG should be diagnosed. Our patient had been in coma without focal motor or generalized tonic-clonic seizure; however, EEG showed no epileptiform discharges even without the use of any sedative or antiepileptic drugs.…”
Section: Discussionmentioning
confidence: 99%